THE EFFECTIVITY OF ADDITION CHEST MOBILIZATION OR PURSED LIP BREATHING IN CONVENTIONAL THERAPY IN COPD PATIENTS - Fidyatul Nazhira (Sport and Fitness Journal, 2021)
Background:COPD is an accumulation of pulmonary pathologies that causes limited air flow, then breathlessness. Chest mobilization and pursed lip breathing (PLB) are physiotherapy management aimed at reducing pulmonary hyperinflation, thereby increasing FEV1 and improve breathlessness. The purpose of this study was to determine differences in the effectiveness of the addition of chest mobilization or PLB in conventional therapy to an increase in FEV1 and improve breathlessness in COPD patients at Lung Hospital dr. Ario Wirawan Salatiga. Research methods:This study is a true experiment with a pretest and posttest control group design research design. The research subjects numbered 30 people then divided into 3 groups. All groups were given treatment 3 times a week for 6 weeks. Group I received additional chest mobilization intervention, group II received additional PLB intervention and group 3 received hospital intervention (conventional). FEV1 was measured using spirometry and tightness was measured using a modified Borg scale. Results:Based on the results of the Wilcoxon sign rank test there was an increase in FEV1 and improve breathlessness with p>0.05 in group 1. In group 2 there was also an increase in FEV1 and improve breathlessness with p> 0.05. In group 3 there was an increase in FEV1 but there was no improve breathlessness. Different test results after the intervention on increasing FEV1 between groups based on the Kruskal-Wallis t-test obtained p> ??0.05. Different test for reduction of tightness after intervention between groups 1 and 2 using the Mann Whitney U test p value > 0.05. So there is no difference in the effect of adding chest mobilization interventions or PLB and conventional therapy. Conclusion:The addition of chest mobilization or PLB to conventional therapy is as good as conventional in increasing FEV 1 and improve breathlessness in COPD patients at Lung Hospital Dr. Ario Wirawan Salatiga. Keyword: COPD; Breathlessness; FEV 1; Chest Mobilization; Pursed Lip Breathing